Rapid DNA-based analytical techniques to verify the authenticity of Halal food - Mustafa, Shuhaimi; Syahmi Sam-on, Muhamad Firdaus (2022)
The halal food industry across the world is experiencing a period of extraordinary growth and development. However, violation of the principle of halal for profit is a major concern as Muslims are only allowed to consume halal food. Recent episodes of adulteration and illegal halal labeling of food products indicated that food fraud is reaching global scales. Therefore, ensuring the authenticity of halal food is a crucial step that all must seriously implement. Compared to protein- and lipid-based techniques, DNA-based authentication is reported to be accurate, sensitive, and reliable. Moreover, DNA has a good stability at elevated temperature, exists in the entire tissue, and has better variation among organisms. In this paper, several rapid DNA techniques such as multiplex PCR, convection PCR, PCR-RFLP, PCRstrip, real-time PCR, LAMP, nanotechnology, and commercial rapid test kits for the detection of porcine DNA and DNA from other animals for halal verification have been identified and discussed. These advanced methods are needed to ensure that the authorities can provide a halal certificate in a rapid, sensitive, and accurate manner.